2019
DOI: 10.3390/s19081885
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Wearable Sensors at the Shoulder Joint: Combining Wireless Electromyography Sensors and Inertial Measurement Units to Perform Physical Workplace Assessments

Abstract: Background: Workplace adaptation is the preferred method of intervention to diminish risk factors associated with the development of work-related shoulder disorders. However, the majority of the workplace assessments performed are subjective (e.g., questionnaires). Quantitative assessments are required to support workplace adaptations. The aims of this study are to assess the concurrent validity of inertial measurement units (IMUs; MVN, Xsens) in comparison to a motion capture system (Vicon) during lifting tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 37 publications
4
48
0
Order By: Relevance
“…These two muscles were chosen because they are the main agonist in shoulder flexion and abduction. They are also highly implicated in shoulder movement above 90° elevation [ 30 ] and their EMG activities correlate with physical demands of working tasks [ 31 ]. The skin was cleaned using alcohol prior to electrode placement.…”
Section: Methodsmentioning
confidence: 99%
“…These two muscles were chosen because they are the main agonist in shoulder flexion and abduction. They are also highly implicated in shoulder movement above 90° elevation [ 30 ] and their EMG activities correlate with physical demands of working tasks [ 31 ]. The skin was cleaned using alcohol prior to electrode placement.…”
Section: Methodsmentioning
confidence: 99%
“…The validity of assessing motion accuracy of IMUs has been confirmed. Poitras et al [24] confirmed the criterion validity of a commercial IMU system (MVN Awinda system, Xsens) by comparing it to a gold standard optoelectronic system (Vicon). Compared to low-cost IMS, IMU has certain advantages in environmental adaptability and a sufficient range of motion.…”
Section: Introductionmentioning
confidence: 97%
“…In the last few years, a new generation of inertial measurement units (IMUs) has emerged, significantly impacting on motion tracking research due to their ease of use, relative low cost, and portability [ 22 , 23 , 24 ]. This technology, taking advantage of recent progress in miniature inertial sensors, consists of lightweight, non-invasive, wearable, wireless sensing units, which open a new opportunity to capture human motion in different settings [ 13 , 25 ].…”
Section: Introductionmentioning
confidence: 99%